2018
DOI: 10.1002/cam4.1465
|View full text |Cite
|
Sign up to set email alerts
|

Tumor‐derived extracellular vesicles activate primary monocytes

Abstract: Tumor cells educate immune effector cells in their vicinity by releasing factors that manipulate their phenotype and function. In fact, the thus generated immunosuppressive tumor microenvironment constitutes an integral part and a hallmark of solid tumors and contributes significantly to tumor development and immune escape. It has long been thought that soluble factors like prostaglandin E2 and TGF‐β are the main mediators of these effects. But tumor cells also constantly release large number of extracellular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 27 publications
0
17
0
Order By: Relevance
“…Tumor-derived soluble mediators such as chemokines (CCL2, CCL5, CXCL12), colony-stimulating factor-1 (CSF-1), TGF-β, IL-10, prostaglandin E2 (PGE2) and metabolites (lactate) likely contribute to the development of TAMs with M2-like phenotype and tumor-promoting properties [16]. Recent studies indicated that, in addition to soluble factors, tumor-derived exosomes could also modulate macrophage cytokine profile and phenotype [1721]. However, little is known about how TRAPs affect macrophage polarization and function in vitro and in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…Tumor-derived soluble mediators such as chemokines (CCL2, CCL5, CXCL12), colony-stimulating factor-1 (CSF-1), TGF-β, IL-10, prostaglandin E2 (PGE2) and metabolites (lactate) likely contribute to the development of TAMs with M2-like phenotype and tumor-promoting properties [16]. Recent studies indicated that, in addition to soluble factors, tumor-derived exosomes could also modulate macrophage cytokine profile and phenotype [1721]. However, little is known about how TRAPs affect macrophage polarization and function in vitro and in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…In line with these results, Bretz et al demonstrated that the stimulation of THP-1 cells by exosomes of cancerous and non-cancerous origin occurred through a TLR (toll-like receptor) dependent mechanism [42]. Furthermore, tumor-derived sEVs have been shown to activate primary monocytes [43]. We used sEVs isolated from a well-established melanoma cell line (A375), as well as from patient-derived primary melanoma cell lines.…”
Section: Discussionmentioning
confidence: 88%
“…It is widely recognized that abnormalities in cytokine expression are implicated in tumorigenesis as they promote growth, reduce apoptosis and facilitate invasion and metastasis of cancer cells 41,42 . Moreover, it has been reported that tumor‐derived EVs induce in primary monocytes an activated phenotype, which is also observed in tumor‐associated macrophages 43 .…”
Section: Discussionmentioning
confidence: 95%